Antibacterial activity of resin rich plant extracts - Mohd Shuaib; Abuzer Ali; Mohd Ali; Bibhu Prasad Panda; Mohd Imtiyaz Ahmad (Wolters Kluwer Medknow Publications, 2013)
Background: The in vitro antibacterial activity of resin rich methanolic extracts (RRMEs) of Commiphora myrrha, Operculina turpethum, and Pinus roxburghii. Materials and Methods: Different concentration were studied by agar-well diffusion method against Gram-positive (Staphylococcus aureus, Bacillus subtilis, Micrococcus luteus, Enterococcus faecalis) and Gram-negative bacterial strains (Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysenteriae). Results: Among all the bacterial strains tested, E. faecalis was most sensitive and S. typhi was resistant to C. myrrha and P. roxburghii. The extracts of O. turpethum were active against all tested strains in which B. subtilis and S. aureus were the most sensitive. Conclusion: This suggested that the antibacterial activity of RRMEs of O. turpethum was more than C. myrrha and P. roxburghii. This probably explains the potential of these plants against a number of infections caused by bacterial strains tested.